Analysis of the Needs of the Visually Impaired in the Social Rehabilitation Services and Technical Means of Rehabilitation According to the Medical and Sociological Research - M. A. Sevastianov; I. A. Bozhkov; V. S. Luchkevich; L. A. Кarasaeva; O. S. Molchanova (Oftalʹmologiâ, 2019)
Purpose: to conduct an analysis of the needs for social rehabilitation services and technical means of rehabilitation for visually impaired people in St. Petersburg. Materials and methods. A medical-sociological study was carried out on a specially developed questionnaire, which makes it possible to analyze the needs of the visually impaired in socio-rehabilitation activities and technical means of rehabilitation. Also, the official state statistical reporting data were used: «forms 7-sobes» for 2015–2016. The study included 250 people. at the age of 18–80 years, who had a disability in sight. Results. The overwhelming majority of visually impaired people (98.4 %) have disabilities of groups I and II. The proportion of disabled people in group II is the highest and amounts to 62.2 %, the proportion of disabled people in group III is the lowest — 1.6 %. Among the total number of employees, the greatest share was occupied by the disabled of the I group (41.7 %), more than half of whom (54.9 %) had no professional education. The majority of visually impaired people (62.8 %) preferred to receive social and rehabilitation services in a center specialized in the Center for Medical and Social Rehabilitation of the Visually Impaired in St. Petersburg. The need for sanatorium treatment for disabled people was significant — 73.2 %, but it was satisfied in 7.2 %. It is established that the real needs of the visually impaired in various types of technical means of rehabilitation are much greater than those suggested in the «Federal List of Rehabilitation Measures, Technical Remedies and Services Provided to the Disabled». In St. Petersburg, about 50.0 % of the visually impaired need high-tech rehabilitation equipment, for example, in a mobile phone, computer or laptop, etc. But due to their absence in the federal and regional lists, they are forced to purchase at their own expense. The conclusion. It is advisable to provide social and rehabilitation services for visually impaired people on the basis of specialized centers (departments) that have a more diverse set of services for the most complete satisfaction of their needs. The needs for sanatorium treatment are minimally satisfied, which makes it necessary to improve the system of organization of sanatorium-and-spa treatment. For the visually impaired, the need for technical means of rehabilitation is satisfied at 75.0 %, which is the basis for considering the issue of expanding the range of the Federal List.